2020
DOI: 10.1002/arp.1782
|View full text |Cite
|
Sign up to set email alerts
|

What over 100 drillings tell us: a new method for determining the Koenigsberger ratio of soils from magnetic mapping and susceptibility logging

Abstract: We investigate the relative fractions of remanent and induced magnetization of the fillings of neolithic long pits in order to develop remanent magnetization as an additional parameter for the archaeological interpretation of magnetic maps. We determine the Koenigsberger ratiothe ratio between induced and remanent magnetization intensitiesfor key targets by combining magnetic mapping with downhole measurements of susceptibility, numerical modelling, and inversion computations. The susceptibility data were acqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
(91 reference statements)
0
2
0
Order By: Relevance
“…We can exclude magnetic mineralogy changes in the grave soil, which could lead to magnetic enhancement. Despite of possible waterlogging conditions on the bottom of the grave pit, decomposition of soil organic matter or buried human body in the presence of magnetotactic bacteria is unlikely to play significant role as it could be in cases with high content of organic matter (Linford, 2004; Pickartz et al, 2020).…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We can exclude magnetic mineralogy changes in the grave soil, which could lead to magnetic enhancement. Despite of possible waterlogging conditions on the bottom of the grave pit, decomposition of soil organic matter or buried human body in the presence of magnetotactic bacteria is unlikely to play significant role as it could be in cases with high content of organic matter (Linford, 2004; Pickartz et al, 2020).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The remanent versus induced magnetization ratio for archaeological soils is reported to be in the range of Q ~ 1 (Bevan, 2016; Fassbinder, 2015; Smekalova et al, 2016). Pickartz et al (2020) showed the importance of remanent magnetization for the magnetization of organic‐rich soil‐filled pits, sourcing magnetic anomalies of low intensity. Numerical calculation of weak magnetic anomalies from soil infill must therefore consider the remanent magnetization of soils.…”
Section: Introductionmentioning
confidence: 99%